Structuration analysis of collaboration in Big Data Analytics work practices in organizations - Dhlamini, Mpumelelo (Department of Information Systems, 2024)
Background: Big Data's emergence has presented organizations with numerous opportunities, such as Big Data Analytics (BDA), which generates insight across multiple departments, interrelated business domains, and organizational levels and provides an opportunity for collaboration. Problem Statement: Organizations face challenges in adopting collaboration across departments for leveraging Big Data due to structural practices in BDA work practices, making it a difficult concept to implement for fostering innovation and long-term competitiveness. Research Purpose: Little is known about the influence of structural practices on collaboration in BDA work practices in organizations. The purpose of this study explores how structures enable and constrain collaboration in BDA work practices. Methodology: The study adopted an interpretivist research philosophy. A qualitative research strategy was employed, using semi-structured interviews for data collection, among 12 (twelve) IT and Analytics professionals. Guided by the initial proposed conceptual framework, grounded theory methodology techniques were adopted to analyze the data, using the NVivo software. Findings: The study identified structural practices in both formal and informal collaboration in BDA work practices. For the formal collaboration, the structures include BDA platform services enacted in practice, BDA capabilities enacted in practice, and governance and management enacted in practice. For the informal collaboration, the structures include ad-hoc BDA platform services enacted in practice, social capabilities enacted in practice, and social contracts and informal sessions enacted in practice. The practical enactment of these structures leads to both intended and unintended consequences, resulting in either enabling or constraining collaboration in BDA work practices. Research Contribution: The study provided an understanding of the structures that enable and constrain collaboration in BDA work practices in organizations. Practitioners in BDA domains can leverage this understanding in their collaboration implementation and assessment. The findings can assist in understanding and defining fit-for-purpose collaboration. Also, a revised conceptual framework and a causal loop diagram presenting the dynamic interplay of collaboration and the structures were presented, with theoretical propositions.